A Study Of The Influence Of Activation Temperature Of Press Mud On The Engineering Properties Of Peat Soil - Lai, Qin Yao (2022)
Peat soil covers 8% of the land area in the world and is an expansive soil which normally classified as problematic soil due to its geotechnical drawback characteristics. Press mud (PM) is the residue of filtration of sugarcane juice from the sugar manufacturing industry that can be used in soil stabilisation. This study proposes an investigation of the influence of stabiliser and activation temperature on the engineering properties of peat soil. The stabilisers used in this study are lime and press mud, and the designed stabilisers proportion is 3% and 5.5% for lime and 0.0%, 0.25%, 0.50%, 1.0% and 2.0% for press mud. Lime was mixed with different percentages of press mud and peat soil in the mixing process to carry out laboratory tests: Standard Proctor Test and Unconfined Compressive Strength Test. Standard Proctor Test was conducted to determine the effects of mixed proportions of lime and press mud on the optimum moisture content and maximum dry density of treated peat soil. Meanwhile, the Unconfined Compressive Strength Test was conducted to determine the effects of mixed proportions of lime and press and the influences of activation temperature on the unconfined compressive strength of treated peat soil. The optimum moisture content and maximum dry density of treated peat soil were obtained at 5.5% lime and 0.25% press mud stabilised peat soil specimen. The optimum moisture content and maximum dry density have an inverse relationship where increases in optimum moisture content will lead to a decrease in maximum dry density. The addition of lime is to neutralise the peat soil and improve its load bearing capacity and PM was added to accelerate the reaction but both lime and press mud did not showed a significant effect. The unconfined compressive strength of treated peat soil showed a significant early strength development by 5.5% lime and 0.25% press mud stabilised peat soil. Lime improve the soil by improving its workability and load bearing capacity which are the important properties for flocculation while PM accelerate the strength development at the beginning stage. The warm activator accelerates the early strength gain of treated peat soil but affects the strength gain negatively in the long period as the continuous high temperature is detrimental to the soil structure and thus, reduces the strength development.